Penerjemahan Komunikatif Kitab Aqidah Al-Tifli Al-Muslim Karya Amr Abdul Mun’im Bin Salim - Muhammad Saukani; Muhammad Anas; Darsita Suparno; M Zaki Mubarak; Kaula Fahmi (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2023)
This study aims to determine the translation of the book 'Aqîdah al-Tifli al-Muslim, which was translated from Arabic into Indonesian using the communicative method and to find out how to apply the strategy in translating the book 'Aqîdah al-Tifli al-Muslim with the communicative method, considering This book discusses the Aqidah of Tauhid which is a very basic science in religion that Muslims must know. The method used in this study is a qualitative method with a descriptive approachbased on research on the text 'Aqîdah al-Tifli al-Muslim as the . After translating the data object as a whole, academic accountability is carried out by applying the communicative translation method and the strategies used in the translation. The results of this study are that six translation strategies are used to translate the book; throw away/hadzf 35%, replace/tabdil 20%, prioritize and end/taqdim wata'khir 23%, add/dziyadah 20%, transposition 8%, and modulation 4%. So this shows that the communicative method for translating the book 'Aqîdah al-Tifli al-Muslim is very effective and suitable because the communicative method is a translation method that produces translations that are acceptable to readers, and each resulting translation provides conformity of the information contained in ST with TT and generate communicative language so that it is easily understood and digested by speakers of the target language.